1998
DOI: 10.1097/00004424-199807000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxic Effects of Iobitridol and Iohexol on the Kidney

Abstract: These findings suggest that iobitridol has significantly less toxic effects on the kidney compared with iohexol under the condition of our experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The observation that female patients in this study suffered significantly more adverse events than males is likely to be due to a higher prevalence of allergies in females. Since most published data on CM involved very low numbers of patients [2][3][4][5] , a prediction on the clinical safety of CM in a large patient population can only be made with caution. The rate of serious adverse events in our larger multicentre study population was 0.002%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that female patients in this study suffered significantly more adverse events than males is likely to be due to a higher prevalence of allergies in females. Since most published data on CM involved very low numbers of patients [2][3][4][5] , a prediction on the clinical safety of CM in a large patient population can only be made with caution. The rate of serious adverse events in our larger multicentre study population was 0.002%.…”
Section: Discussionmentioning
confidence: 99%
“…Low-osmolar CM are also better tolerated by the patient than high-osmolar substances, especially with regard to non-serious adverse events [2][3][4] . Iobitridol is a tri-iodinated low-osmolar non-ionic CM that exhibits excellent tolerability and low toxicity in intravenous urography and has been approved in Germany since 1996 [5,6] .…”
mentioning
confidence: 99%
“…The iobitridol molecule is characterised by a high level of 3D stability of the hydrophilic groups around the lipophilic tri-iodinated benzene ring. The results of preclinical, toxicological, and clinical trials can be found in a supplement of "Acta Radiologica" dedicated to this topic [8] and various other international journals [9,10,11,12]. This article presents the results of a postmarketing surveillance study based on the data of a total of 61,745 patients having received this contrast medium.…”
Section: Contrast Medium Injectionmentioning
confidence: 99%
“…Previous studies using renal cortical slices have demonstrated that PAH accumulation was inhibited by many kinds of nephrotoxic agents, including antibiotics, 13,18 heavy metals, 18 and Pt-containing anticancer drugs. 5,19 Wasaki et al 20 studied the effects of nonionic CM on PAH accumulation in rat renal slices and reported that iobitridol, a newly developed nonionic CM, had a significantly smaller effect on PAH accumulation than iohexol. Those earlier experiments demonstrated that determinating the PAH accumulation in renal slices is a reliable method for evaluating the effects of nephrotoxic agents on the metabolic function of renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%